Non-clinical similarity of biosimilar ABP 798 with rituximab reference product. (July 2021) - McBride, Helen J.; Jassem, Shea; Chow, Vincent; Kanakaraj, Palanisamy; Lebrec, Herve; Kuhns, Scott; Ferbas, John; Wong, Min; Thway, Theingi M.
Abstract: ABP 798 is a biosimilar to Rituxan® (rituximab reference product [RP]). Non-clinical assessments relevant to the primary and secondary mechanisms of action (MOA) contribute to the totality of the evidence (TOE) in supporting biosimilarity and are critical in providing scientific evidence for extrapolation of indications. Similarity of ABP 798 with rituximab RP was investigated across a range of biological activities which have potential impact on pharmacokinetics and clinical efficacy with non-clinical assessments relevant to MOA such as CD20 internalization, trogocytosis, binding to primary human natural killer (NK) cells as well as the ability to induce antibody-dependent cellular phagocytosis (ADCP) in peripheral blood mononuclear cells. Additionally, in vitro synergy of ABP 798 or RP with chemotherapeutic agents, in vivo xenograft studies in mice, and toxicological assessments in cynomolgus monkeys (including B cell depletion and toxicokinetics) were also conducted. Results from these non-clinical assessments contribute to the TOE supporting the biosimilarity between ABP 798 and rituximab RP across a range of primary and secondary MOAs and support justification for extrapolation to all indications of use for ABP 798 for which the RP is approved.